2018
DOI: 10.1109/jphot.2018.2872985
|View full text |Cite
|
Sign up to set email alerts
|

Design of Ultra Large Normal Dispersion ZBLAN Photonic Crystal Fiber and Its Application in Mid-IR Ultra Short Fiber Lasers

Abstract: A ZBLAN photonic crystal fiber (PCF) with normal dispersion is theoretically designed and investigated. The designed PCF can provide a large normal dispersion coefficient and a low confinement loss in a broad wavelength range of 1.8-3.6 μm. Especially, the PCF exhibits an ultra large normal dispersion value of −351.3 ps/km/nm and a small confinement loss of 0.05 dB/m at 2.9 μm. By using the designed PCF as a dispersion compensator in a mode-locked ZBLAN fiber laser, stretched pulse with compressed pulse durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To accelerate the convergence of the calculation, initial cavity condition is set to be a 10 ps chirp-free pulse with energy of 100 aJ [30]. The peak power and the central wavelength of the initial pulse are ∼9.4 μW and 2000 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To accelerate the convergence of the calculation, initial cavity condition is set to be a 10 ps chirp-free pulse with energy of 100 aJ [30]. The peak power and the central wavelength of the initial pulse are ∼9.4 μW and 2000 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have shown that a nearly zero flattened chromatic dispersion profile in the band 2 to 3.5 μm can be achieved through a proper design of the PCF cladding region. Furthermore, Gao et al 14 designed a ZBLAN PCF with a large negative chromatic dispersion value of −351.3 ps∕km∕nm and confinement loss as low as 0.05 dB/km at 2.9 μm. In addition, the authors have demonstrated, via numerical simulations, that stretched optical pulses with a compressed duration of 1.56 ps are realized using the proposed PCF as a dispersion compensator device in a mode-locked fiber laser.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have shown that a nearly zero flattened chromatic dispersion profile in the band 2 to 3.5 μm can be achieved through a proper design of the PCF cladding region. Furthermore, Gao et al 14 . designed a ZBLAN PCF with a large negative chromatic dispersion value of 351.3 ps/km/nm and confinement loss as low as 0.05 dB/km at 2.9 μm.…”
Section: Introductionmentioning
confidence: 99%